(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Cervical cancer begins when healthy cells on the surface of the cervix change or get infected with human papillomavirus (HPV) and grow out of control, forming a mass called a tumour. Long-term infection of HPV on the cervix can result in cancer, leading to a mass or tumour on the cervix. A tumour can be cancerous or benign. A cancerous tumour is malignant, meaning it can spread to other parts of the body. A benign tumour means the tumour will not spread1 . objective:1)To assess the knowledge on cervical cancer and its prevention among women attending PAP Smear and HPV-DNA screening camp. 2)To find out the association of knowledge score on cervical cancer and its prevention among women attending PAP Smear and HPV-DNA screening camp with their selected Socio-demographic variables. Research design: The research design adopted for the study is diagrammed as: Assess the knowledge on cervical cancer and its prevention. Analysis& Results: Major findings of the study are presented under following sections and headings: The obtained data are organized and presented in the following sections:1)Analysis and Interpretation of the demographic variables of the samples such as Age, Religion, Education, Marital status, No. of children in terms of frequency and percentage.2)Analysis and Interpretation of the data related to the Knowledge of the Samples on cervical cancer and its prevention among women attending PAP Smear and HPV-DNA screening camp 3)Analysis and Interpretation of the data related to association of knowledge scores with selected demographic variables of the samples